Sound localization circuits in reptiles - Han, Dawei; Fuquen, Rebeca W.; Willis, Katie L.; Christensen-Dalsgaard, Jakob; Carr, Catherine E. (Frontiers in Amphibian and Reptile Science, 2024)
Location of sound sources is a fundamental task of the auditory system. Recent studies have shown that land vertebrates employ an array of sound localization strategies. We have therefore compared auditory brainstem circuits by measuring cell numbers in the cochlear nuclei in relation to brain weight among different groups of reptiles to determine if these behavioral differences are reflected in the organization of the brainstem. In extant archosaurs, the birds and crocodilians, the two ears are weakly connected pressure receivers, and sound direction is computed by binaural interactions in brain involving parallel processing of interaural time and level differences. The first-order cochlear nuclei are nucleus magnocellularis (NM) and nucleus angularis (NA). NM projects bilaterally to the nucleus laminaris (NL), where interaural time differences are computed in archosaurs. Relative to brain size, NA, NM and NL cell counts of the American alligator (Alligator mississippiensis) are similar to those of birds. Testudines (turtles and tortoises), sister group to archosaurs, are also assumed to compute sound location from binaural interactions in the brain due to weakly connected middle ears. Compared to archosaurs, NA, NM and NL of the red-eared slider (Trachemys scripta), common snapping turtle (Chelydra serpentina) and Hermann’s tortoise (Testudo hermanni) are all proportionally small. In lizards, due to the strong internal coupling of the middle ears, the cochlear nerve responses are directional, and interaural time and level differences are co-dependent and frequency dependent, suggesting that the neural processing of sound direction may be different from archosaurs. Compared to archosaurs, NM and NL of the tokay gecko (Gekko gecko) and green iguana (Iguana iguana) are proportionally small, but NA is well-developed, suggesting a greater importance of the NA pathway for the processing of the high-frequency directional information generated by the coupled ears. Snakes originated from lizard ancestors, but have secondarily lost their eardrums, and their sound localization strategies are unknown. NA and NM of the western ratsnake (Pantherophis obsoletus) are proportionally smaller than those of the lizards.